Preetis Farsan Food Ordering System - Balachandran, Monisha; Nazri Mohd Nawi (Applied Information Technology And Computer Science, 2022)
This paper describes the development of a food ordering system for Preetis Farsan Enterprise.This system is tailored to the enterprise's specific requirements for smooth and efficient operations. Preetis Farsan Enterprise may also provide sales and profit-making reports on a weekly and monthly basis. This system is being developed using a waterfall-based methodology. The PHP programming language was used to create the system. After the project is completed, the administrator and customer burdens will be decreased as a result of this project. The solution will have a dashboard with its own independent sections that will make it easier for both parties to order meals and review other data. There will be an additional degree of security against, fraud, and theft because the new system will contain a register and login module. Furthermore, any human error will be removed with a simple click of a button